Sevoflurane and isoflurane anaesthesia in acute abdomen canine patients - SINGH, G D; JADON, N S; HUSSAIN, AUBID; SHARMA, V K (The Indian Journal of Animal Sciences, 2010)
The present study was aimed to prepare a suitable anaesthetic combination of sevoflurane or isoflurane in acute abdomen critically ill canine patients. Acute abdomen was due to anatomical anomalies and due to lodgement of foreign bodies in the animals of group A and B respectively. The animals of group C were the normal healthy dogs used as control. These animals were further divided into 2 sub groups AI, All, BI and BII. The animals of subgroup AI, BI, and CI were subjected to administration of anaesthetic combination of atropine sulphate @ 0.04 mg/kg body weight, diazepam @ 1 mg/kg body weight, I.M. thiopental sodium @ 10–12 mg/kg body weight I.V. (just to pass endotracheal tube) and sevoflurane (3–3.5%) while the animals of sub group AII, BII and CII were subjected to the administration of anaesthetic combination of atropine sulphate @ 0.04 mg/kg body weight, diazepam @ 1 mg/kg body weight, I.M. and thiopental sodium @ 10–12 mg/kg body weight I.M. just to pass endotracheal tube, followed by isoflurane (2–2.5%). The efficacy of anaesthetic combinations was determined by observing different clinicophysiological and haematobiochemical parameters. There was a complete muscle relaxation in all the groups of animals. Corneal, palpebral reflexes were completely depressed during the surgical anaesthesia. An increase in heart rate and total erythrocyte count along with a decrease in respiration rate, rectal temperature, respiratory minute volume, haemoglobin, packed-cell volume, total leucocyte count and neutrophil count was observed during the period of anaesthesia. A gradual decrease in the mean values of total protein, albumin, gamma glutamyl transferase and calcium was observed during anaesthesia. These changes were less pronounced in group subjected to sevoflurane as compared to isoflurane. On the basis of the findings observed in this study it was concluded that the combination of thiopental sodium and sevoflurane was more safe as compared to the combination of thiopental sodium and isoflurane as it provides more cardiac and respiratory stability.